Acquired obesity and poor physical fitness impair expression of genes of mitochondrial oxidative phosphorylation in monozygotic twins discordant for obesity - Mustelin, Linda (American Physiological Society, 2008)
Defects in expression of genes of oxidative phosphorylation in mitochondria have been suggested to be a key pathophysiological feature in familial insulin resistance. We examined whether such defects can arise from lifestyle-related factors alone. Fourteen obesity-discordant (BMI difference 5.2 ± 1.8 kg/m(2)) and 10 concordant (1.0 ± 0.7 kg/m(2)) monozygotic (MZ) twin pairs aged 24–27 yr were identified among 658 MZ pairs in the population-based FinnTwin16 study. Whole body insulin sensitivity was measured using the euglycemic hyperinsulinemic clamp technique. Transcript profiles of mitochondrial genes were compared using microarray data of fat biopsies from discordant twins. Body composition of twins was determined using DEXA and maximal oxygen uptake (V̇o(2max)) and working capacity (W(max)) using a bicycle ergometer exercise test with gas exchange analysis. The obese cotwins had lower insulin sensitivity than their nonobese counterparts (M value 6.1 ± 2.0 vs. 9.2 ± 3.2 mg·kg LBM(−1)·min(−1), P < 0.01). Transcript levels of genes involved in the oxidative phosphorylation pathway (GO:0006119) in adipose tissue were lower (P < 0.05) in the obese compared with the nonobese cotwins. The obese cotwins were also less fit, as measured by V̇o(2max) (50.6 ± 6.5 vs. 54.2 ± 6.4 ml·kg LBM(−1)·min(−1), for obese vs. nonobese, P < 0.05), W(max) (3.9 ± 0.5 vs. 4.4 ± 0.7 W/kg LBM, P < 0.01) and also less active, by the Baecke leisure time physical activity index (2.8 ± 0.5 vs. 3.3 ± 0.6, P < 0.01). This implies that acquired poor physical fitness is associated with defective expression of the oxidative pathway components in adipose tissue mitochondria.